Green operation practices for MSIC operators at the east coast Peninsular Malaysia Marine Park Islands - Yusof, Zeenat Begam; Jamaludin, Mariam; Ibrahim, Mansor (Institut Pengajian Siswazah, Universiti Teknologi MARA, 2018)
The Marine tourism industry is one of the most significant economic sectors in Malaysia due to the country's richness in marine biodiversity. For the past two decades, Marine Park Islands (MPIs) in Peninsular Malaysia have been receiving high numbers of tourist arrivals. Overdevelopment of tourist accommodations on the MPIs is causing rapid degradation of marine ecological assets. Three issues were identified. The issues are (a) overdevelopment of the Micro and Small Island Chalets (MSICs) on the East Coast of Peninsular Malaysia MPIs which causes cumulative negative impacts on the marine ecological assets, (b) low performance of green operation practices by MSIC operators and (c) shortcoming in the management of the East Coast Peninsular Malaysia MPIs by related local authorities. Limited literatures are available regarding the issues. Therefore, the aim of this thesis is to provide appropriate recommendations for the three key, which will help to reduce the degradation of the East Coast Peninsular Malaysia MPIs' marine ecological assets. Four objectives were outlined. The first objective is to identify and analyse the negative impacts of the MSICs operation on the marine ecological assets of the East Coast Peninsular Malaysia's MPIs. The second objective is to determine MSICs green operation practices performance levels. The third objective is to investigate the most significant barriers faced by the MSIC operators in performing green operation practices and the last objective is to recognised the management barriers faced by the local authorities in managing the Tioman, Perhentian, Redang and Kapas Island. Data were collected using mixed method approach such as combination of qualitative and quantitative method involving several strategies such as survey questionnaire, semi-structured interviews, structured observations and document analysis. As for the first research question, this study identifies that five operation activities of the MSICs are causing significant negative impacts on the islands marine ecological assets. The operation activities are external works, improper management of solid waste, excessive extraction of groundwater, in efficient use of sewerage system and use of diesel based energy system. Finding for second research question indicate that MSIC operators have low performance of green operation practices. Finding for the third research question indicated that seven factors are identified as the most significant barriers. Finding for the fourth research question indicated that six common and three specific management barriers are faced by the related local authorities. About 190 appropriate recommendations was identified from the four research questions which are grouped into technical and management solutions. The solutions are able to help MSIC operators and local authorities to manage the East Coast Peninsular Malaysia MPIs sustainably. The outcome of this thesis help to produce an appropriate green operation practices manual for the East Coast Peninsular Malaysia MSIC operators. The outcomes also contribute to the existing body of knowledge in the area of Agenda 21, sustainable development concept, and small and medium tourism enterprises